2016
DOI: 10.18632/oncotarget.10486
|View full text |Cite
|
Sign up to set email alerts
|

High expression of WISP1 in colon cancer is associated with apoptosis, invasion and poor prognosis

Abstract: Colon cancer (CC) likes many epithelial-derived cancers, resulting from a complex tumorigenic process. However, the exactly mechanisms of development and progression of CC are still unknown. In this study, integrated analysis in the GSE33113 and Fudan University Shanghai Cancer Center Hospital datasets revealed that WISP1 expression was significantly increased in CC cases, positivity correlated with the advanced pathologic stage and a poor prognosis was more likely in CC patients with higher levels of WISP1. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 43 publications
4
56
0
Order By: Relevance
“…Furthermore, in the clinic, WISP1 expression levels are generally higher in tumors than in normal tissues (Gurbuz & Chiquet-Ehrismann, 2015) and high WISP1 levels in primary tumors correlate with shorter periods of distant metastasisfree survival in a number of cancers, including breast, gastric, ovarian, colorectal, and oral squamous cell carcinomas (Clausen et al, 2016;Wu et al, 2016). In support of this idea, our data indicate that knockdown of Wisp1 in tumor cells prevents collagen linearization and inhibits metastasis.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, in the clinic, WISP1 expression levels are generally higher in tumors than in normal tissues (Gurbuz & Chiquet-Ehrismann, 2015) and high WISP1 levels in primary tumors correlate with shorter periods of distant metastasisfree survival in a number of cancers, including breast, gastric, ovarian, colorectal, and oral squamous cell carcinomas (Clausen et al, 2016;Wu et al, 2016). In support of this idea, our data indicate that knockdown of Wisp1 in tumor cells prevents collagen linearization and inhibits metastasis.…”
Section: Discussionsupporting
confidence: 67%
“…A correlation between high WISP1 expression and shorter distant metastasis-free survival was also observed for patients with luminal A breast cancers (Fig 5D), whereas no correlation was found for patients with luminal B breast cancer subtype ( Fig 5E). Furthermore, high levels of WISP1 also associate with faster disease progression and poor prognosis of other cancer types, such as gastric (Fig 5F), ovarian (Fig 5G), and colorectal cancer (Wu et al, 2016), as well as oral squamous cell carcinoma (Clausen et al, 2016). Furthermore, high levels of WISP1 also associate with faster disease progression and poor prognosis of other cancer types, such as gastric (Fig 5F), ovarian (Fig 5G), and colorectal cancer (Wu et al, 2016), as well as oral squamous cell carcinoma (Clausen et al, 2016).…”
Section: High Wisp1 Gene Expression Levels Correlate With Poor Prognomentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in a report published in 2016, Wu et al took a fresh look at the issue 30. They found that higher levels of CCN4 expression in human colon cancer cases were associated with a poor prognosis.…”
Section: Colon Cancermentioning
confidence: 99%
“…Multiple studies have reported that WISP1 can stimulate cell adhesion [30, 31]. In addition, both WISP1 and MUC1 were reported to promote cell adhesion via activating EMT process.…”
Section: Discussionmentioning
confidence: 99%